Implementasi Teori Keperawatan Comfort/Kenyamanan Kolcaba Dalam Manajemen Kecemasan Pasien Kanker: Literature Review - Aprillia Esti Sawestri; Fitriana Suprapti (Universitas Pahlawan Tuanku Tambusai, 2025)
Cancer is a disease that not only causes physical impacts but is also closely associated with various psychosocial challenges, one of which is anxiety faced during diagnosis and treatment. This literature review aims to identify and summarize publications related to the application of Kolcaba's theory to anxiety management in cancer patients through various nursing interventions, such as therapeutic communication, health education, relaxation techniques, and providing social support. The literature review was conducted by selecting articles published between 2014 and 2023 from three major databases: Gale, PubMed, and ProQuest. This review used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach to systematically screen articles.. Based on the review results, fifteen articles (n = 15) were found that discussed nursing interventions to address anxiety in cancer patients utilizing Kolcaba's theory. Supportive care through exercisebased rehabilitation, music therapy, spiritual-based palliative care interventions, guided imagery and progressive muscle relaxation, advanced planning, comprehensive education and care can reduce anxiety. The implementation of Kolcaba's Comfort Theory has been shown to contribute to improving patients' quality of life, particularly in reducing negative psychological symptoms such as anxiety and depression. Therefore, the application of this theory needs to be continuously developed through optimal nursing services to achieve hospital service goals